Proceedings of Computer Graphics International 2018 2018
DOI: 10.1145/3208159.3208162
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Cloth Simulation using Deep Neural Networks

Abstract: Fast and reliable physically-based simulation techniques are essential for providing flexible visual effects for computer graphics content. In this paper, we propose a fast and reliable hierarchical cloth simulation method, which combines conventional physically-based simulation with deep neural networks (DNN). Simulations of the coarsest level of the hierarchical model are calculated using conventional physically-based simulations, and more detailed levels are generated by inference using DNN models. We demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Saito et al [SUM14] proposed an upsampling technique that adds physically feasible microscopic detail to coarsened meshes by considering the internal strain at runtime. More recently, Oh et al [OLL18] have shown how to train a deep neural network to upsample low-resolution cloth simulations.…”
Section: Related Workmentioning
confidence: 99%
“…Saito et al [SUM14] proposed an upsampling technique that adds physically feasible microscopic detail to coarsened meshes by considering the internal strain at runtime. More recently, Oh et al [OLL18] have shown how to train a deep neural network to upsample low-resolution cloth simulations.…”
Section: Related Workmentioning
confidence: 99%
“…Yan et al takes images as input and uses a neural network to encode the rope state as a set of connected nodes, and apply a bi-directional LSTM to capture the dynamics based on the node representations [10]. For 2D cloth-like objects, a physically-based simulator and fullyconnected networks are combined to perform the simulation [11] and [12] for coarse and fine levels respectively. PlaNet [13] encodes the images by an Autoencoder as a latent code and predicts the future latent representation based on GRU structure.…”
Section: A Deformable Object Dynamics Modelingmentioning
confidence: 99%
“…Chen et al [CYJ ∗ 18] trained a CNN akin to image super resolution to upsample low resolution cloth to high resolution in texture space. Oh et al [OLL18] train fully connected networks (FCNs) for subdividing a triangle into 4 triangles and upsampling the cloth simulation. They average the outputs of the edge vertices predicted by the network on adjacent triangles.…”
Section: Related Workmentioning
confidence: 99%
“…Kavan et al [KGBS11] constrained the low resolution simulation to match the high resolution at low frequencies and trained a linear upsampling operator, optionally with oscillatory modes. During run-time Seiler et al [SSH12] [OLL18] train fully connected networks (FCNs) for subdividing a triangle into 4 triangles and upsampling the cloth simulation. They average the outputs of the edge vertices predicted by the network on adjacent triangles.…”
Section: Related Workmentioning
confidence: 99%